Effect of interferon alpha on high serum androgen concentrations in HIV positive men with Kaposi's sarcoma. Issue 4 (April 1997) - Christeff, N; Gharakhanian, S; Thobie, N; Wirbel, E; Dalle, M T; Costagliola, D; Nunez, E A; Rozenbaum, W
Abstract : AIM: To measure serum androgen concentrations in men with HIV related Kaposi's sarcoma (KS) who had been treated with recombinant interferon (IFN) alpha-2a to determine the role of androgens on the development of KS lesions. METHODS: 32 men with HIV related KS who had been treated with IFN were studied: 24 men in complete KS remission and eight not in remission. Serum androgen concentrations were determined before, during, and after IFN treatment and correlated with clinical remission. RESULTS: All patients in complete KS remission had lower serum androgen concentrations following IFN treatment: -51% for dehydroepiandrosterone (DHEA) (p < 0.0001); -38% for DHEA sulphate (p < 0.002);-39% for androstenedione (p < 0.002); and -44% for testosterone (p < 0.007). These decreases brought the serum concentrations to about normal levels. However, IFN had varying effects on serum androgen concentrations in the men not in remission: a small decrease, a large increase in one androgen, or no change in serum androgens. CONCLUSIONS: The association between serum androgen levels and the progression or remission of HIV associated KS suggests that androgens affect the development of KS lesions. A clear understanding of the changes in the androgen environment may provide a sound basis for the development of new therapeutic strategies.